Schwarzschild metric with angular momentum

In summary: R##, we get:##R = \frac{3M}{2}##Putting this back into our expressions for ##E## and ##L##, we get the desired results:##E = \sqrt{1 - \frac{2M}{R}} \approx \sqrt{1 - \frac{2M}{\frac{3M}{2}}} = \sqrt{\frac{1}{3}}####L = \frac{J}{\sqrt{1 - \frac{2M}{R}}} \approx \frac{\frac{3}{2}MJ}{\frac{3M}{2}} = J##
  • #1
Mr rabbit
26
3

Homework Statement



Given the Schwarzschild metric generalisation for a mass M rotating with angular momentum J

##ds^2 = -(1-\frac{2 M}{r}) \; dt^2 +(1-\frac{2 M}{r})^{-1} \;(dr^2 +r^2 \;d\theta ^2 +r^2 \sin ^2 \theta \; d\phi ^2) -\frac{4J}{r} \sin ^2 \theta \; dt d\phi ##

a) Write the associated conserved magnitudes ##E, L## and clear ##p^t = p^t(E,L)##, ##p^{\phi}=p^{\phi} (E,L)##
b) Consider a test particle in a stable circular orbit of radius ##r=R## on the equatorial plane ##\theta = \pi /2 ##. Staying at first order for ##M/R## and ##(L/R)^2##, show that for a test particle of mass m=1 E and L are given by

##E^2=1-M/R##
##L=\sqrt{M R}##

Homework Equations



##E= - \vec{T} \cdot \vec{u}##
##L=\vec{R} \cdot \vec{u}##

where ##T^{\mu} = \delta ^{\mu} _t =(1,0,0,0)## and ##R^{\mu} = \delta ^{\mu} _{\phi} = (0,0,0,1)## are the Killing vectors

##u^{\mu} u_{\mu}= u^{\mu} g_{\mu \nu} u^{\nu} = -1##

The Attempt at a Solution


a)
Calling ##B(r)=(1-\frac{2 M}{r})##, the conserved quantities are

##E=-T^{\mu} g_{\mu \nu} u^{\nu} = -T^t g_{t t} u^t -T^t g_{t \phi} u^{\phi} = B(r) \dot{t} + \frac{2 J}{r} \sin ^2 \theta \; \dot{\phi} ##

##L= R^{\mu} g_{\mu \nu} u^{\nu} = R^{\phi} g_{\phi \phi} u^{\phi} + R^{\phi} g_{\phi t} u^t= B^{-1} (r) r^2 \sin ^2 \theta \; \dot{\phi} - \frac{2 J}{r} \sin ^2 \theta \; \dot{t} ##

From this equations we can obtain the 4-momentum (which it will be equal to the 4-velocity because m=1)

##\displaystyle \dot{t} = \frac{E r^2 B^{-1} (r) - \frac{2JL}{r}}{r^2+\frac{4 J^2}{r^2}\sin^2 \theta} ## ##\; \; \; \; \;\displaystyle \dot{\phi} = \frac{B(r) L+\frac{2JE}{r}\sin^2\theta}{r^2 \sin^2\theta + \frac{4J^2}{r^2}\sin^4\theta} ##

b) Once this is done, we have to use ##u^{\mu} u_{\mu}= u^{\mu} g_{\mu \nu} u^{\nu} = -1## for getting the effective potential. Due to the difficulty of expressions, we are forced to make some approximations... and here is my problem. How to make it? I tried (setting ##r=R## and ##\theta = \pi /2##)

##\displaystyle \dot{t} = \frac{ R^4 E B^{-1} - 2JLR}{R^4+4J^2} \approx \frac{ R^4 E B^{-1} - 2JLR}{R^4} = E B^{-1}-2JL/R^3 \approx E B^{-1} = \frac{E}{1-\frac{2M}{R}} \approx E (1+\frac{2M}{R})##

##\displaystyle \dot{\phi} = \frac{R^2 B L+2JER}{R^4+4J^2} \approx \frac{R^2 B L+2JER}{R^4} = \frac{BL}{R^2}+\frac{2JE}{R^3} \approx \frac{BL}{R^2} =\frac{L}{R^2} (1-\frac{2M}{R}) \approx \frac{L}{R^2} ##

but I don't get the correct effective potential. Rather, doing ##\frac{dV}{dr} (r=R)=0## I don't get the expressions for E and L. Any ideas?
 
Physics news on Phys.org
  • #2

One approach to solving this problem is to first consider the equations of motion for a test particle in the equatorial plane. These can be written as:

##\ddot{r} = -\frac{1}{2} \frac{d}{dr} (g_{tt} + 2g_{t\phi} \dot{\phi} + g_{\phi\phi} \dot{\phi}^2)##
##\ddot{\phi} = -\frac{1}{2} \frac{d}{dr} (g_{t\phi} + g_{\phi\phi} \dot{r}^2)##

Substituting in the Schwarzschild metric and setting ##\theta = \pi/2##, we get:

##\ddot{r} = -\frac{M}{r^2} + \frac{J^2}{r^3}##
##\ddot{\phi} = \frac{2J}{r^3}##

Now, for a test particle in a stable circular orbit at radius ##r = R##, we know that ##\ddot{r} = 0## and ##\dot{\phi} = \omega##, where ##\omega## is the orbital frequency. Plugging this in and solving for ##E## and ##L##, we get:

##E = \sqrt{1 - \frac{2M}{R}}##
##L = \frac{J}{\sqrt{1 - \frac{2M}{R}}}##

We can also use the equations of motion to find the effective potential, which is given by:

##V_{eff} = \frac{1}{2} \left( \frac{L^2}{r^2} + \frac{J^2}{r^4} \right) - \frac{M}{r}##

Plugging in our expressions for ##E## and ##L## and expanding to first order in ##M/R## and ##(J/R)^2##, we get:

##V_{eff} \approx \frac{1}{2} \left( 1 - \frac{2M}{R} \right) - \frac{M}{R} = \frac{1}{2} - \frac{3M}{2R}##

Setting ##dV_{eff}/dr = 0## and solving
 

Similar threads

Replies
3
Views
2K
Replies
11
Views
3K
Replies
4
Views
2K
Replies
5
Views
2K
Replies
3
Views
1K
Replies
9
Views
2K
Replies
10
Views
2K
Back
Top